Strengthening The Quality of Human Resources (HR) In Improving The Quality of Islamic Education in Madrasah - Mohammad Zaini (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2021)
his paper aims to strengthen human resources (HR) which is of course very important in improving the quality of Islamic education. In this era of global competition, the trend of education is experiencing a shift in orientation that places human development as a whole through education and training of various types, levels, characteristics and forms. The education of Indonesian people as a whole is idealized to be the culmination point of achieving the national education which has so far been the dream of the Indonesian people. The idolized personal figure has not yet been produced, so educational institutions are used as alternative expectations, as the main instrument of the humanitarian and humanitarian process, namely respecting and giving freedom of opinion and expression. Such appreciation is a seed that begins to grow, and as a process freedom is constantly being fought for. The pattern of educational leadership in increasing human resources must be pursued through Islamic education that can be developed through transformational and charismatic leadership in madrasas supported by institutional strength, business networks and bureaucratic networks.